Pengaruh daun kelor dan dislipidemia terhadap kuantitas sperma - Dahril; Muhammad Puteh Mauny; Munandar, Rudi Haris (Journal of Medical Science, 2021)
Infertility is a global health problem affecting 1 of 10 couples in the world and its related to dyslipidemia. Dyslipidemia, as metabolic syndrome, had become global epidemic. It is estimated 12-37% Asian population and 12-26% of European population had dyslipidemia. Dyslipidemia decreased sperm count by increasing free radical oxygen species (ROS) caused of lypotoxicity and lipid peroxidation. Antioxidant is treatment choice for this problem. Drum stick (Moringa oleifera L) is medical herb that contain antioxidant compound such as alkaloid, flavonoid, tannin, vitamin C, E, and steroid. So, Moringa oleifera L leaf could protect sperm cells from free radicals of dyslipidemia and become alternative treatment for infertility. It was a post-test only control group design. Sample consist of 30 rats devided into 6 groups. It began with atherogenic diet to induce dyslipidemia. Then, Ethanol extract of Moringa oleifera L leaf was given. Sperm count was calculated microscopically with Neubauer chamber. Data analysis was using one way analysis of variance (ANNOVA) test, then continued with post hoc Duncan test. There were significant differences of total cholesterol, triglyceride, high density protein, low density protein, and sperm count between groups based on one way ANNOVA test (p < 0,05). On post hoc Duncan test, Dyslipidemia induction decreased sperm count compared to other groups. Ethanol extract of 200 mg/body weight and 400 mg/body weight leaf had no difference effect compared to atorvastatin. Ethanol extract of 800 mg/body weight leaf increased sperm count significantly compared to other groups.